2017
DOI: 10.3126/hren.v13i1.17951
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of fall injuries in senior people attending emergency ward in BPKIHS, a tertiary level hospital, Dharan, eastern region of Nepal

Abstract: Background: The Senior or elderly population is rapidly growing in Nepal. They sustain injuries

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…and South India, where 13% participants reported a fall in the past. 13,18 However, a study conducted in United Arab Emirates showed that about half of the respondents had a history of fall in the past two years 4 and found significant association. 7,16 Similarly, present study found that the level of fall risk is statistically significant with age and vision problem (p=<0.05).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…and South India, where 13% participants reported a fall in the past. 13,18 However, a study conducted in United Arab Emirates showed that about half of the respondents had a history of fall in the past two years 4 and found significant association. 7,16 Similarly, present study found that the level of fall risk is statistically significant with age and vision problem (p=<0.05).…”
Section: Discussionmentioning
confidence: 98%
“…9,10 Fractures, contusions, abrasions, and lacerations are the physical consequences of falls. 11,12 The cost of treatment is high in fall related injuries 13 and causes a huge burden to family and also the society in terms of healthcare utilization and costs. 14 Moreover, fall injury is the leading cause of premature death among people of 65 and older.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with the finding of study done in Nepal and South India, where 13% participants reported a fall in the past. 13,18 However, a study conducted in United Arab Emirates showed that about half of the respondents had a history of fall in the past two years 4 and found significant association. 7,16 Similarly, present study found that the level of fall risk is statistically significant with age and vision problem (p=<0.05).…”
Section: Discussionmentioning
confidence: 98%
“…Despite the significant risk of a fall injury, national-level studies on fall-related deaths and injuries are lacking. Most of the studies were based on a small sample population or were hospital-based (Gupta et al, 2015;Limbu & Poudyal, 2020;Rai et al, 2017). A country representative study can provide the national situation of fall injuries and act as evidence for highlighting the need to develop effective fall preventive measures.…”
Section: Introductionmentioning
confidence: 99%